Obtaining Compositions Based on Sulphur for Road Building Materials - Fozilov S.F.; Mavlanov B.A.; Raupov B.K; Khayrullayev Ch.K. (Genius Journals, 2024)
The article examines the production of a sulfur-based composition for road building materials. The use of sulfur compositions and polymer sulfur compounds with a modifier in the production of filled road materials will improve their properties and provide the opportunity to sell additional volumes of elemental sulfur on the domestic market, since the production of road materials is a very capacious and intensively developing branch of national industry
Keywords: compositions; polymers; consumption; chemical industries